Daratumumab plus bortezomib, lenalidomide and dexamethasone for transplant-ineligible or transplant-deferred newly diagnosed multiple myeloma: the randomized phase 3 CEPHEUS trial - Usmani, Saad Z; Facon, Thierry; Hungria, Vania; Bahlis, Nizar J; Venner, Christopher P; Braunstein, Marc; Pour, Ludek; Martí, Josep M; Basu, Supratik; Cohen, Yael C; Matsumoto, Morio; Suzuki, Kenshi; et al. (Nature medicine, 2025)
Frontline daratumumab-based triplet and quadruplet standard-of-care regimens have demonstrated improved survival outcomes in newly diagnosed multiple myeloma (NDMM). For patients with transplant-ineligible NDMM, triplet therapy with either daratumumab plus lenalidomide and dexamethasone (D-Rd) or bortezomib, lenalidomide and dexamethasone (VRd) is the current standard of care. This phase 3 trial evaluated subcutaneous daratumumab plus VRd (D-VRd) in patients with transplant-ineligible NDMM or for whom transplant was not planned as the initial therapy (transplant deferred). Some 395 patients with transplant-ineligible or transplant-deferred NDMM were randomly assigned to eight cycles of D-VRd or VRd followed by D-Rd or Rd until progression. The primary endpoint was overall minimal residual disease (MRD)-negativity rate at 10-5 by next-generation sequencing. Major secondary endpoints included complete response (CR) or better (≥CR) rate, progression-free survival and sustained MRD-negativity rate at 10-5. At a median follow-up of 58.7 months, the MRD-negativity rate was 60.9% with D-VRd versus 39.4% with VRd (odds ratio, 2.37; 95% confidence interval (CI), 1.58-3.55; P < 0.0001). Rates of ≥CR (81.2% versus 61.6%; P < 0.0001) and sustained MRD negativity (≥12 months; 48.7% versus 26.3%; P < 0.0001) were significantly higher with D-VRd versus VRd. Risk of progression or death was 43% lower for D-VRd versus VRd (hazard ratio, 0.57; 95% CI, 0.41-0.79; P = 0.0005). Adverse events were consistent with the known safety profiles for daratumumab and VRd. Combining daratumumab with VRd produced deeper and more durable MRD responses versus VRd alone. The present study supports D-VRd quadruplet therapy as a new standard of care for transplant-ineligible or transplant-deferred NDMM. ClinicalTrials.gov registration: NCT03652064 .
Keywords: dexamethason; lidé; Middle Aged; Adult; Female; Multiple Myeloma; Dexamethasone; lenalidomid; Humans; Antibodies, Monoclonal; protokoly protinádorové kombinované chemoterapie; Progression-Free Survival; Neoplasm, Residual; reziduální nádor; monoklonální protilátky; doba přežití bez progrese choroby; lidé středního věku; bortezomib; mužské pohlaví; mnohočetný myelom; Bortezomib; Lenalidomide; ženské pohlaví; Aged, 80 and over; senioři nad 80 let; Male; Aged; dospělí; Antineoplastic Combined Chemotherapy Protocols; senioři